Application of Agile Development Methods in the Development of Integrated Systems for Vehicle Body Repair - Didik Indrayana; Prajoko; Asril Adi Sunarto (IAIC International Conference Series, 2023)
PT XYZ Auto Body Repair is a company that focuses on repairing and servicing vehicles, especially cars that have been involved in accidents or disasters. Currently, data processing still uses physical forms, which has proven to be inefficient because it takes significant time, labor, and resources. Collecting and inputting data from various forms requires a large effort, while systems that are not integrated cause delays in providing the required information. These challenges impact the company's ability to make decisions quickly and on time, especially in the face of increasingly tight and complex business competition. Therefore, an efficient and integrated solution is needed. Seeing this problem, it was decided to develop an integrated vehicle repair system by applying agile development methods, especially the Extreme Programming model. This approach allows development in an iterative, fast, adaptive manner, and actively involves users at every stage of development. Experience has shown that applying the Extreme Programming model can produce an integrated system that meets user needs in a short time. With this system, companies can produce reports quickly without reduplication or repetitive data processing. All parts involved in the vehicle repair process will be connected to one company server, creating the efficiency and accuracy needed to support business growth in a dynamic business environment.